If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -1x(-4) Reorder the terms for easier multiplication: y = -1 * -4x Multiply -1 * -4 y = 4x Solving y = 4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 4x
| X-4=3x+36 | | (3)(x)=10-2x | | -8x-25=3x | | 2x+3(x+4)=9 | | 17-9y=-13+16y | | (8y-x^2y)dy+(x+xy^2)dx=0 | | 1.5-0.04x=-3.34 | | 6=3-13h | | -3y-8=8y+25 | | (10)(x)+51=56 | | 18x=-2y | | 3(2x+5)-4x=33 | | -1[8+1(-7+1)]+14= | | h^2-7h+4=0 | | -9=5-(8-n) | | 7x+12y=150 | | 4(X-8)=3(X+5) | | 96=8r | | -2(3y-7)=57 | | (m+6)-(m-7)=-9m | | 17=7x+2-2x | | 4w-2s+2w-s+5s= | | -1-2-1= | | 3x^2-44=0 | | -18x+3=-13 | | 24=x+-6 | | 9(2a-3)= | | -3(x+1)=-54 | | -9x+2x-4x=0 | | L=L-3+6 | | 25=1x-10 | | 15=-15x |